2017
DOI: 10.1080/15412555.2016.1256384
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care to Prevent Readmissions for Patients with Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis

Abstract: Readmissions of patients with chronic obstructive pulmonary disease (COPD) to hospitals cast a heavy burden to health care systems. This meta-analysis was aimed to assess the efficacy of continuity of care as interventions, which reduced readmission and mortality rates of such patients. PubMed, Cochrane Library and Embase were searched for articles published before July 2015. A total of 31 reports with randomized controlled trials (RCTs) were finally included in this meta-analysis. The results showed that heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 60 publications
3
70
0
5
Order By: Relevance
“…The proportion of readmissions that could be prevented with better care depends largely on the definition of 'preventable' and the population in question, but it is considerable; in their June 2007 report to the US Congress, the Medical Payment Advisory Commission estimated that 75% of Medicare readmissions are potentially preventable. 82 Much has been written about strategies for reducing readmissions in patients with chronic conditions such as HF and COPD, such as continuity of care and better co-operation with community teams, 83,84 medication reconciliation, 84 self-management, 85 health education, telemonitoring, 83 pulmonary rehabilitation, 86,87 and care bundles, 88 although the evidence base in terms of randomised controlled trials for reducing COPD readmissions is disputed 89 and a multifactorial approach is needed. 84 We also note that our analysis found that mortality and readmission were more likely at hospitals with fewer doctors per bed and that readmission was also more likely at smaller hospitals.…”
Section: Implications For Practice and Translation Of Findingsmentioning
confidence: 99%
“…The proportion of readmissions that could be prevented with better care depends largely on the definition of 'preventable' and the population in question, but it is considerable; in their June 2007 report to the US Congress, the Medical Payment Advisory Commission estimated that 75% of Medicare readmissions are potentially preventable. 82 Much has been written about strategies for reducing readmissions in patients with chronic conditions such as HF and COPD, such as continuity of care and better co-operation with community teams, 83,84 medication reconciliation, 84 self-management, 85 health education, telemonitoring, 83 pulmonary rehabilitation, 86,87 and care bundles, 88 although the evidence base in terms of randomised controlled trials for reducing COPD readmissions is disputed 89 and a multifactorial approach is needed. 84 We also note that our analysis found that mortality and readmission were more likely at hospitals with fewer doctors per bed and that readmission was also more likely at smaller hospitals.…”
Section: Implications For Practice and Translation Of Findingsmentioning
confidence: 99%
“…104 A meta-analysis on continuity of care in COPD published in 2017 identified a comprehensive nursing intervention (including health education, self-management, action plan and home visits/follow-up telephone) as the best intervention, reducing both all-cause and COPD-specific readmissions at 6 and 12 months. 105 In a recent randomized clinical trial, a 3-month program combining transitional care and longterm self-management support not only failed to show a reduction in COPD readmissions at 6 months but showed significantly greater COPD-related hospitalizations and emergency department visits in the intervention group, without an improvement in quality of life. 106 Studies on care bundles to reduce early readmissions have shown the same variability of results.…”
Section: Care Bundlesmentioning
confidence: 99%
“…There was substantial heterogeneity between studies, such as the timing (e.g., pre-discharge vs. post-discharge), frequency (e.g., number of home visits), and how each intervention was delivered (e.g., type and number of personnel conducting interventions). Two studies initiated interventions more than 28 days after hospital discharge Yang 17 Most interventions involved home visits and health education. Three interventions added regulated monthly telephone calls.…”
Section: Prieto-centurion 16mentioning
confidence: 99%